Glucose-conjugated chicken myofibrillar proteins derived from random-centroid optimization present potent hydroxyl radical scavenging activity. Issue 12 (2nd December 2019) - Nishimura, Kimio; Suzuki, Momoka; Saeki, Hiroki
ABSTRACT: The optimal conditions for the preparation of glucose-conjugated chicken myofibrillar proteins (Mfs) via the Maillard reaction, presenting strong antioxidant activity against hydroxyl radicals (･OH) and high solubility in low ionic strength medium, were sought using random-centroid optimization (RCO). Four parameters of temperature, relative humidity (RH), reaction time, and glucose-to-Mfs mixing ratio, were examined, resulting in a total of 24 vertices. Evaluations were carried out relatively to each individual vertex, and the optimal preparatory conditions to obtain the highest antioxidant activity were determined as follows: temperature of 52 °C, RH of 38%, reaction time of 6.79 h, and a glucose to Mfs mixing ratio of 11.7 (w/w). The resulting glucose-conjugated chicken Mfs gained thermal gel-forming ability and its ･OH averting capacity reached 9.7 ± 0.7 μmol of gallic acid equivalent/g of protein. Abbreviations: GA: gallic acid; HORAC: hydroxyl radical averting capacity; IC50 : half-maximal inhibitory concentration; 2-ME, 2-mercaptoethanol; Mfs: myofibrillar proteins; MHC: myosin heavy chain; ･OH: hydroxyl radical; PAGE: polyacrylamide gel electrophoresis; RCO: random-centroid optimization; RH: relative humidity; RLU: relative light units; SDS: sodium dodecyl sulfate; SEM: scanning electron microscope; SS: disulfide Graphical abstract: : Glucose-conjugated chicken myofibrillar proteins derived from random-centroid optimization present potent hydroxyl radical scavenging activity.